Surfactants, Nanomedicines and Nanocarriers: A Critical Evaluation on Clinical Trials - Diego Alejandro Dri; Carlotta Marianecci; Maria Carafa; Elisa Gaucci; Donatella Gramaglia (MDPI AG, 2021)
Advances, perspectives and innovation in drug delivery have increased in recent years; however, there is limited information available regarding the actual presence of surfactants, nanomedicines and nanocarriers in investigational medicinal products submitted as part of a request for authorization of clinical trials, particularly for those authorized in the European Economic Area. We retrieve, analyze and report data available at the Clinical Trial Office of the Italian Medicines Agency (AIFA), increasing the transparency and availability of relevant information. An analysis of quality documentation submitted along with clinical trials authorized by the AIFA in 2018 was carried out, focusing on the key terms "surfactant", "nanomedicine" and "nanocarrier". Results suggest potential indications and inputs for further reflection and actions for regulators to actively and safely drive innovation from a regulatory perspective and to transpose upcoming evolution of clinical trials within a strong regulatory framework.